ANALISIS PENGUASAAN KATA BENDA DALAM BAHASA KHEK PADA MAHASISWA HAKKA PRODI PENDIDIKAN BAHASA MANDARIN - Christiana, Evita; Veronica, Tjen; Afrimonika, Yoanna (Universitas Tanjungpura, 2024)
Hakka is a dialect of Chinese that is still preserved and used among the Chinese community in Indonesia. The purpose of this article is to learn about the conditions of mastery and difficulties in the use of Hakka nouns by students of the Chinese Language Education Study Program, FKIP Tanjungpura University. This research uses test questions and questionnaires to obtain research results. It is known from the test questions that students' understanding of